(3HOGjI GdoeQjOjfs - (3CHh YHO Gddg GdNRQLjs; (3TYjH Hf YHO Gddg Hf SYO Hf YHO GdcGaj GdMQjajT , CHh eOjf,J (B810 (3g` s
(3ChdgG (B:s
(3Chd eG jLH Ydi GdeQjO UMHI GdTjN GdYGde GdYGed s
(3BNQgG (B:s
(3aef Yed HgPg GdBHI obHd Yedg hef NCdagG de ojbHd Yedg fLR cJGH HOGjI GdeQjOjfI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B167 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B302s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B- (3GdeZQH (B(186) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs